2021
DOI: 10.1016/j.amjmed.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Population Decline in COPD Admissions During the COVID-19 Pandemic Associated with Lower Burden of Community Respiratory Viral Infections

Abstract: Background: The COVID-19 pandemic has led to widespread implementation of public health measures, such as stay-at-home orders, social distancing, and masking mandates. In addition to decreasing spread of SARS-CoV2, these measures also impact the transmission of seasonal viral pathogens, which are common triggers of COPD exacerbations. Whether reduced viral prevalence mediates reduction in COPD exacerbation rates is unknown. Methods: We performed retrospective analysis of data from a large, multicent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…12 Another study in the United States showed a positive correlation between COPD admissions and community viral burden. 11 The present study shows that in France, in contrast with what was observed during the pre-pandemic years, the number of hospital admissions for AECOPD did not increase during the winter months of the pandemic, a season when the circulation of VRI is usually high. Furthermore, a considerable increase in flu vaccination coverage was observed in France in 2020 compared with 2019.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…12 Another study in the United States showed a positive correlation between COPD admissions and community viral burden. 11 The present study shows that in France, in contrast with what was observed during the pre-pandemic years, the number of hospital admissions for AECOPD did not increase during the winter months of the pandemic, a season when the circulation of VRI is usually high. Furthermore, a considerable increase in flu vaccination coverage was observed in France in 2020 compared with 2019.…”
Section: Discussioncontrasting
confidence: 68%
“…Two studies found an increased mortality in 2020 compared to pre-pandemic years, of respectively +53% and +130% but both were based on small numbers, 8,16 while others did not find a significant difference. 11,12,14 To date, time trends in in-hospital mortality have not been analysed with large-scale and exhaustive data. Finally, while most studies found a stable proportion of AECOPD stays involving intensive care units (ICU) admission in 2020 compared to previous years, 11,14,16 a cohort study in Denmark found a 36% decrease in the risk of admission to an ICU in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevention guidance has proven effective against the transmission of respiratory diseases. [12,24,25] Our study showed that these guidelines were also effective in reducing the likelihood of FN in patients receiving TAC.…”
Section: Discussionmentioning
confidence: 67%
“…The number of patients hospitalized with asthma showed similar trends from 2017 to 2019, even in studies using databases in Japan [ 8 ], but in 2020 (from the ninth week onward), there was a large decrease compared with the previous 3 years. This decrease could be due to a decrease in cases of viral infection as a result of standard infection control measures, such as face masks and hand disinfection for SARS-CoV-2, restrictions on going out, and other factors [ 9 , 10 ]. The decrease in outpatient and inpatient admissions apart from asthma may also be the result of fewer opportunities for infection.…”
Section: Discussionmentioning
confidence: 99%